2015
DOI: 10.1016/j.febslet.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutagenesis around the CuA site of a polyphenol oxidase from Coreopsis grandiflora (cgAUS1)

Abstract: HighlightsSite-directed mutations of AUS1 around the CuA site were generated and verified.All mutations led to loss of diphenolase activity with butein as substrate.Exchange of histidines in the CuA resulted in enzymes containing only one Cu.F273 mutation to alanine did not increase the monophenolase activity.C97 mutation eliminated the diphenolase activity, but 2 Cu atoms were incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
(139 reference statements)
2
16
0
2
Order By: Relevance
“…The role of Cys97 was also analyzed in aurone synthase from Coreopsis grandiflora (cgAUS1). However, in contrast to TyrAo, in cgAUS1, the replacement of Cys97 to Ala affected protein folding and hindered its activity, but did not have any effect on copper binding …”
Section: Copper In the Binding Sitementioning
confidence: 90%
See 3 more Smart Citations
“…The role of Cys97 was also analyzed in aurone synthase from Coreopsis grandiflora (cgAUS1). However, in contrast to TyrAo, in cgAUS1, the replacement of Cys97 to Ala affected protein folding and hindered its activity, but did not have any effect on copper binding …”
Section: Copper In the Binding Sitementioning
confidence: 90%
“…), the CuB site exhibits higher conservation than CuA . Biochemical investigations of tyrosinases from different species have shown the involvement of the conserved histidine residues in copper binding …”
Section: The Overall Structure Of Tyrosinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research has also shown that polyphenols exhibit pro-oxidant behavior, and could be a carcinogen or mutagen [12][13][14][15][16][17][18]. It has been reported that factors such as pH value of media, the presence of transition metals, or enzymes [19][20][21][22], and, particularly, the complexity of each individual's digestive system [23][24][25] have profound impact on these contradictory results.…”
Section: Introductionmentioning
confidence: 99%